FACEBOOK, TWITTER INSTAGRAM & WHATSAPP SEBAGAI KONSEP NYATA DETERMINISME TEKNOLOGI DALAM MASYARAKAT - Muhammad Muhammad; Saifuddin Arsyen (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
Technological determinism is a theory which asserts that changes that have occurred in technological developments from ancient times to the present have had a major influence on society. Technological developments such as new creations or innovations, new discoveries, and other things aimed at developing technology to facilitate human activities, have a major influence on the development of social values ​​and life in society. Technological determinism is also defined as an autonomous arrangement based on technology which then claims that technology is a dominant factor in the occurrence of social changes, the effects of which depart from the cultural meaning and uses that technology can provide, because basically in technological determinism, The innovations found by inventors in society are also aimed at society. Therefore, technological determinism considers the importance of human ideas in creating technology which then affects human social life.